Objeción de conciencia y desobediencia civil: similitudes y diferencias - Falcón y Tella, María José (Anuario de Derechos Humanos. Nueva Época, 2009)
This article describes a series of convergences and discordant aspects between civil disobedience and conscientious objection. For clarity of exposition, we group the divergences by distinguishing the “who”, the “why”, the “how”, the “what” and the “for-what”, that is the subject, the foundations, the form, the object and the goal of the phenomena in question.